Behind the Stars: Consumer Personality and Review Composition for New and Refurbished Products - Krishnan, Karthik; Rana, Arunima (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The rapid growth of e-commerce and technological advancements has amplified the production of electronic waste (E-waste). Refurbished products offer a sustainable alternative by extending product lifecycles, yet consumer behavior toward these products remains underexplored in many regions, including India. This study investigates key product attributes and psychological characteristics of consumers, analyzing 2,189 refurbished and 4,967 new product reviews using text mining and linguistic analysis tools. The findings highlight significant differences in consumer preferences, with refurbished product consumers prioritizing Battery health, Service-related aspects, packaging, and hygiene, while new product buyers emphasize features and aesthetic factors. Psychological differences are evident as refurbished product consumers exhibit a more positive tone and goal-driven reasoning while the new product consumers show more structured analytical evaluation. Using Constructive Decision-Making Theory (CDMT), the study explains how consumers of refurbished products construct satisfaction by reinforcing their choices post-purchase. The findings offer insights for refurbishers, policymakers, and marketers to foster trust and adoption of refurbished products through marketing strategy, standardized practices, and certifications while aligning with consumers’ decision-making process.